Counting of People in the Extremely Dense Crowd using Genetic Algorithm and Blobs Counting - Muhammad Arif; Sultan Daud; Saleh Basalamah (IAES International Journal of Artificial Intelligence (IJ-AI), 2013)
In this paper, we have proposed a framework to count the moving person in the video automatically in a very dense crowd situation. Median filter is used to segment the foreground from the background and blob analysis is done to count the people in the current frame. Optimization of different parameters is done by using genetic algorithm. This framework is used to count the people in the video recorded in the mattaf area where different crowd densities can be observed. An overall people counting accuracy of more than 96% is obtained.DOI: http://dx.doi.org/10.11591/ij-ai.v2i2.1793